2011
DOI: 10.1177/1049909111423774
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Services as a Key Outcome in Amyotrophic Lateral Sclerosis (ALS) Care

Abstract: People with amyotrophic lateral sclerosis (ALS) frequently express dissatisfaction with services. Patient satisfaction with services in ALS care is not always measured and service user perspectives are not usually included when evaluating the outcomes of care. There is a lack of consensus on what constitutes satisfaction for patients in ALS care. To date, health care professionals' conceptualization of outcomes in ALS care has excluded measures of patient satisfaction with services. Exploring the context of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 78 publications
(141 reference statements)
2
18
0
Order By: Relevance
“…Studies of service users recruited from specialized ALS clinic settings have indicated high levels of satisfaction with dedicated multidisciplinary care 32,61. However, rigorous assessment of patient satisfaction with specialized multidisciplinary ALS care is yet to be conducted,42 and there is a need to explore the benefits to patients of specialized multidisciplinary ALS services in addition to survival times and health outcomes 57…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of service users recruited from specialized ALS clinic settings have indicated high levels of satisfaction with dedicated multidisciplinary care 32,61. However, rigorous assessment of patient satisfaction with specialized multidisciplinary ALS care is yet to be conducted,42 and there is a need to explore the benefits to patients of specialized multidisciplinary ALS services in addition to survival times and health outcomes 57…”
Section: Discussionmentioning
confidence: 99%
“…However, well-timed decision-making remains a challenge for health professionals and patients 17,37,38. Specialized multidisciplinary clinical ALS services have emerged to provide a supportive environment for collaborative and patient-centered care,39,40 yet the impact of specialized multidisciplinary ALS services on decision-making is unknown 41,42. Additionally, there has been no evaluation of the benefits that specialized clinics provide in terms of patient satisfaction42 or patient-clinician relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of patients and carers in decision-making are distinct from those of health professionals,83 and require exploration to identify their distinct perspectives. More broadly, there has been no examination of the impact of specialized multidisciplinary ALS care on patient satisfaction,36 or health professional satisfaction and well-being. The emotional and professional difficulties faced by ALS and palliative care clinicians41 may be better supported within a dedicated model of ALS care.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined patient-centered care in specialized multidisciplinary ALS clinic settings,36 and we know very little of health professional experiences within multidisciplinary ALS care. A small number of studies of clinician perspectives have revealed the ethical, emotional, and professional difficulties encountered in managing patient deterioration 34,3741.…”
Section: Introductionmentioning
confidence: 99%